2018
DOI: 10.14366/usg.18006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of first-trimester intrauterine hematoma on adverse perinatal outcomes

Abstract: PurposeThe aim of this study was to evaluate whether the presence of an intrauterine hematoma (IUH) on an early pregnancy ultrasound scan showing a live fetus was related to adverse perinatal outcomes.MethodsWe performed a retrospective cohort study to evaluate pregnant women who underwent an ultrasound examination in early pregnancy, between 6 weeks 0 days and 10 weeks 6 days. We compared the perinatal outcomes between women with and without firsttrimester IUH using the Mann-Whitney and Fisher exact tests. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…found that chorioamnionitis was more common in women with a persistent IUH. The findings of studies assessing the association between first-trimester miscarriage and IUH are conflicting, with some showing no increased risk 1,7 and others an increased risk of miscarriage 5,6,37 . Previous studies have also suggested that the presence of IUH before 7 or 8 weeks' gestation is associated with a higher risk of miscarriage 8,38 .…”
Section: Discussionmentioning
confidence: 99%
“…found that chorioamnionitis was more common in women with a persistent IUH. The findings of studies assessing the association between first-trimester miscarriage and IUH are conflicting, with some showing no increased risk 1,7 and others an increased risk of miscarriage 5,6,37 . Previous studies have also suggested that the presence of IUH before 7 or 8 weeks' gestation is associated with a higher risk of miscarriage 8,38 .…”
Section: Discussionmentioning
confidence: 99%
“…The outcome measures of ongoing pregnancies such as gestational week at delivery, birth weight, and delivery route, were also similar both group of patients of first trimester bleeding with or without subchorionic hematoma. 15 In this study, 20% pregnancies with first trimester bleeding with hematoma had preterm deliveries and 7.7% in pregnancies with first trimester bleeding without hematoma progressed to preterm delivery. Palatnik et al showed the occurrence of preterm birth to be more in patients with subchorionic hematoma and it was found to be 12.5%.…”
Section: Discussionmentioning
confidence: 54%
“…14 Peixoto et al in their retrospective cohort study found the incidence of intrauterine hematoma to be 4.5% (35 of 783 pregnancies) and also observed a higher proportion (28.6%) of miscarriage in pregnancy with intrauterine hematoma than those without intrauterine hematoma (10%). 15 We found that first trimester bleeding with presence of subchorionic hematoma was associated with increased risk of preeclampsia, fetal growth restrictions, preterm birth, non-reassuring fetal heart rate pattern, caesarean delivery and low birth weight baby when compared to patients with first trimester bleeding without hematoma. This higher risk of antenatal complications and preterm birth the pregnancy with first trimester bleeding along with hematoma was reflected as occurrence of nonreassuring fetal heart rate pattern, increased rate of caesarean delivery and low birth weight, however there was no significant difference in 5 minutes Apgar score and the NICU admission, in the babies of either group.…”
Section: Discussionmentioning
confidence: 75%
“…However, Li et al [21] evaluated the case-control and cohort studies of the years 2000-2015 in their meta-analyses and observed that SCH caused an increased risk of spontaneous miscarriage but was not related to PL in ongoing pregnancies. Peixoto et al [22] reported increased miscarriage risk in the patients having SCH in the first trimester. Avi et al [23] reported that there was not a significant relationship between the 2D measurement of SCH, vaginal bleeding, and adverse pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%